2002
DOI: 10.1243/095440502760291844
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a new wrist joint replacement prosthesis—a multidisciplinary approach

Abstract: The wrist joint is highly complex and there remain unresolved problems to be overcome in designing a successful wrist joint prosthesis. Consequently, the results of total wrist joint replacements have been poor compared to those for hip and knee joint replacements. A multidisciplinary team of orthopaedic surgeons and engineers is working at Bath to tackle some of the key issues in the engineering of a new wrist joint prosthesis. Following a brief background to the work being undertaken by the group, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…One of the main advantages of the control strategy was the use of specimen-specific muscle moment arms about the wrist axes as custom inputs. This accounted for the variations in APL observed across specimens, due to the presence of multiple distal tendon slips ( Thwin et al, 2014 ), which is one of the possible reasons for the omission of the APL during in vitro testing on other simulators reported in the literature ( Dimitris et al, 2015 , Erhart et al, 2012 , Farr et al, 2013 , Leonard et al, 2002 ). However, the variations of the APL moment arm about the FE and adduction-abduction axes of the carpometacarpal joint ( Smutz et al, 1998 ) were not considered in this study, since the position of the first metacarpal was not actively controlled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main advantages of the control strategy was the use of specimen-specific muscle moment arms about the wrist axes as custom inputs. This accounted for the variations in APL observed across specimens, due to the presence of multiple distal tendon slips ( Thwin et al, 2014 ), which is one of the possible reasons for the omission of the APL during in vitro testing on other simulators reported in the literature ( Dimitris et al, 2015 , Erhart et al, 2012 , Farr et al, 2013 , Leonard et al, 2002 ). However, the variations of the APL moment arm about the FE and adduction-abduction axes of the carpometacarpal joint ( Smutz et al, 1998 ) were not considered in this study, since the position of the first metacarpal was not actively controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it also acts as a stabiliser of the wrist during active FE in vivo ( Kauer, 1980 ). Despite this, the APL is often neglected during the simulation of wrist motions using physiological wrist simulators ( Dimitris et al, 2015 , Erhart et al, 2012 , Farr et al, 2013 , Leonard et al, 2002 ). However, results from multiple cyclic planar and complex wrist motions simulated in this study, with and without the APL, showed that its absence resulted in alterations in the force distribution across the wrist muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A test protocol for finger implants has been proposed following the development of a finger joint simulator [68]. Details on the development of a wrist simulator have been described [69].…”
Section: Validationmentioning
confidence: 99%
“…In active simulators, the tendons are loaded using controllable electromechanical, hydraulic, or pneumatic actuators. Both feed-forward [3] and feedback [1], [2], [7] control architectures have been used for wrist motion creation. The redundancy in the human musculature poses a challenge in calculating muscle forces to move the joint.…”
Section: Introductionmentioning
confidence: 99%